The mythical Mediterranean sea : crossroads of cultures, people, and civilizations - Ceramella, Nick; Gori, Umberto (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2019)
This volume brings together papers presented at the 7th Annual International Conference co-organised by Florence University of the Arts, Italy, and Stony Brook University (SUNY), USA. The contributors explored the many connections that define the Mediterranean Sea as a symbol of tradition and modernity, and examined it as a region capable of congregating, synergizing and transforming cultures. Their writings focus on the relationship between the cultural, social, and historical environment of Mare Nostrum to pinpoint the elements defining its identity. Hence, particular emphasis is placed on the role and relevance of the Mediterranean as the first beacon of multi-ethnicity which may be seen as a symbol of diversity and unity, as well as a model that holds clues to understanding the global merging of cultures. As such, it is a real shame to see that the general interest in this unique and fascinating area has arisen not thanks to such highly positive features, but because, as Pope Francis says, it has become an open-air cemetery where thousands of people keep drowning
The Mediterranean Sea: inexhaustible source of inspiration for British literature and culture / Nick Ceramella -- Gianni Clementi's Finis Terrae: shaping transnational subjectivities in the Mediterranean / Stefano Muneroni -- Cultural aspects of "Mare Nostrum": Italy seen through the eyes of the Greek poet Yannis Ritsos -- Sensuousness and silence: Ungaretti and Camus: comparing two Mediterranean authors / Sara Moran -- Writing Mediterranean history: from geohistory to floating signifiers / William Boelhower -- Mediterranean democracy and the United States during the Cold War: Italy's 1976 elections and the citizens' alliance for Mediterranean freedom / Stefano Luconi -- Coexistence and clash: Convivencia and pragmatic pluralism in the medieval Mediterranean / Mark T. Abate -- Negotiating trade: merchant manuals and cross-cultural exchange in the medieval Mediterranean / Joseph F. Stanley -- Nineteenth-century photography of the Mediterranean between reality and imagination / Emanuela Sesti -- "Una faccia, una pancia?" Mediterranean culinary encounters in contemporary film / Harry Kashdan -- "De Re Mediterranea" in Germany? Ludwig I and the classical reinvention of Munich, 1825-1848 / Jeffrey Gaab -- Changing life styles in Mediterranean countries: towards a homogenization of habits, values and cultures? / Sandra Nannini and Elena Radicchi -- The Mediterranean identity of Montenegro / Boris Vukicevic -- Vast, diverse and equally immutable: sonice notes on the Mediterranean / Antonio Pellegrino -- Identity concept within the Mediterranean framework operation, Mare Nostrum: creating an emerging Mediterranean identity / Jema Stellato Pledger
Includes bibliographical references
Print version record
eBooks on EBSCOhost
Keywords: Mediterranean Region -- Social conditions -- 20th century; Mediterranean Region -- Social conditions -- 21st century; Popular culture -- Mediterranean Region -- History -- 20th century; Political culture -- Mediterranean Region -- History -- 21st century; Méditerranée, Région de la -- Conditions sociales -- 20e siècle.; Méditerranée, Région de la -- Conditions sociales -- 21e siècle.; HISTORY -- World; Political culture; Popular culture; Social conditions; Mediterranean Region; 1900-2099; History